Tourism value VS barriers to booking trips online. (March 2020) - San-Martín, Sonia; Jiménez, Nadia; Liébana-Cabanillas, Francisco
Abstract: The purpose of this research is twofold. Firstly, this study examines the influence of economic, social, physical, and technological attributes associated with tourism on the role played by personal characteristics such as anxiety, perceived risk and experience in booking trips online on online purchase intention and electronic word-of-mouth (e-WOM). Secondly, this study analyzes the moderating effect of use contexts (desktop computer vs. smartphone/tablet). Results revealed that the values attributed to tourism anxiety, risk, and experience positively affected online purchase intention and e-WOM, therefore confirming the proposed moderation effect. Highlights: The aim of this research is to examine the online purchase of travel tickets. We include influence of economic, social, physical, and technological values attributed to tourism. Moreover, we analyze the role of anxiety, perceived risk and the online experience of buying trips. Additionally, the moderating effect of use contexts will be analyzed. The study has important implications for professionals and for institutions.